Factors associated with anemia in school teenagers: A cross-sectional study (Research, Society and Development, 2021)
Introduction: Iron deficiency anemia is a public health problem with significant prevalence among adolescents. This pathology causes a reduction in the concentration of serum hemoglobin, compromising the transport of oxygen to body tissues, causing fatigue, reduced cognitive function, delay in weight-statural growth and motor development, in addition to causing damage to the immune system, to performance physical at all stages of life. Objective: To identify the factors associated with the prevalence of anemia in adolescents from public schools. Methods: Cross-sectional, descriptive, retrospective study, with a sample of 512 school adolescents. Socioeconomic and demographic information, results of blood tests and C-reactive protein (PCR) tests were used, as well as anthropometric and food consumption data. Results: In the sample, there was a prevalence of anemia in female adolescents 20 (3.9%) p-value (0.0013). Adolescent food consumption was inadequate in fruits and vegetables. Conclusion: The main factor associated with the prevalence of anemia was the female sex.